ANALISA PERBANDINGAN EASYHOTSPOT DAN MIKROTIK DALAM PENERAPAN HOTSPOT AREA DENGAN SISTEM AAA - Lubis, Rizal Fakhruddin; Raharjo, Suwanto; Sutanta, Edhy (Jurnal Jarkom, 2014)
ABSTRACT At present more and more public places are provided hotspots area in order to attract consumers. Such facilities are generally only be used by a particular user is allowed, so needed a software to authenticate the prospective user prior to access to the Internet using hotspots area. Many alternative software options available, so that the necessary guidelines for choosing the right software to do security, one with the AAA system (Authentification, Authorized, Accounting). This study compared two software namely EasyHotspot and Mikrotik for the implementation of the AAA system in hotspot areas. Keywords: EasyeHotspot, Mikrotik, hotspots, internet.